The Case for Using Hydrogen Peroxide Contact Lens Care Solutions: A Review. Issue 2 (March 2019) - Nichols, Jason J.; Chalmers, Robin L.; Dumbleton, Kathy; Jones, Lyndon; Lievens, Christopher W.; Merchea, Mohinder M.; Szczotka-Flynn, Loretta
Abstract : Abstract: Despite their established disinfection and safety benefits, the use of hydrogen peroxide (H2 O2 ) lens care systems among today's wearers of reusable contact lenses remains low in comparison with multipurpose solution (MPS) use. Multipurpose solution systems, however, present several potential drawbacks that may impact patient outcomes, including the use of chemical preservatives for disinfection, biocompatibility issues, and challenges with respect to lens care compliance. Given their unique composition and mechanism of action, one-step H2 O2 systems offer the opportunity to avoid many of the challenges associated with MPS use. This article reviews the evolution of H2 O2 lens care systems and examines the current scientific and clinical evidence regarding the relative ease of use, lens and tissue compatibility, disinfection efficacy, and ocular surface safety of H2 O2 systems. Evaluation of the available data indicates that in comparison with MPS, one-step H2 O2 systems tend to promote more favorable compliance, efficacy, comfort, and ocular surface outcomes for a wide range of contact lens–wearing patients. Based on the current published evidence, the authors recommend that eye care practitioners consider making one-step H2 O2 systems their first-line contact lens care recommendation for most wearers of reusable lenses.